Творческий вклад И.Я. Франко в развитие украинской культуры - Сенченко, Н.А. (Культура народов Причерноморья, 2014)
Автор исследует творческий вклад Ивана Яковлевича Франко в развитие украинской науки и культуры. В статье обращено внимание на многоплановость и глубину открытий и исследований нашего соотечественника. Проанализировано развитие идеи о национальной литературе. Показано, что идея единства, национальной справедливости, являющаяся лейтмотивом творчества Ивана Яковлевича, пронизывает и другие сферы жизни общества. Выявлен его вклад в развитие психологии, который заключается в установлении общих закономерностей креативного процесса, его определяющих и составных частей во всей их внутренней динамике. Показано, что его философские помыслы носили сугубо рационалистический характер, причем, с опорой не только на достижения частных наук, но главное – на логику и историю научного анализа и мышления, ибо только разуму для продуктивной работы необходима добрая и свободная воля человека. Автор досліджує творчий внесок Івана Яковича Франка в розвиток української науки і культури. У статті звернено увагу на багатоплановість і глибину відкриттів і досліджень нашого співвітчизника. Проаналізовано розвиток ідеї про національну літературу. Показано, що ідея єдності, національної справедливості, що є лейтмотивом творчості Івана Яковича, пронизує і інші сфери життя суспільства. Виявлено його внесок у розвиток психології, котрий полягає у встановленні загальних закономірностей креативного процесу, його визначальних і складових частин у всій їх внутрішній динаміці. Показано, що його філософські помисли носили суто раціоналістичний характер, причому, з опорою не тільки на досягнення приватних наук, але головне – на логіку та історію наукового аналізу і мислення, бо тільки розуму для продуктивної роботи необхідна добра і вільна воля людини. The article indicates that the formation of the Ukrainian state is impossible without profound analysis of Ukrainian culture. Names Taras Shevchenko, Lesia Ukrainka, Ivan Franko known not only in Ukraine, but also worldwide. The study of their work often goes in the direction of literature, leaving a circle consideration the scientific contribution of individual representatives of the Ukrainian cultural elite. Namely awareness of the extent of scientific discoveries made by our great predecessors, brings a sense of pride and patriotism in the hearts of his contemporaries. The author explores the creative contribution of Ivan Franko Ukrainian development in science and culture. The article drew attention to the diversity and depth of discovery and exploration of our compatriot. Analyzes the development of the idea of a national literature. It is shown that the idea of unity, national justice, which is the leitmotif of creativity Ivan Franko penetrates other spheres of social life. Revealed his contribution to the development of psychology , buyout is to establish the general laws of the creative process , its determinants and components in all their internal dynamics. Shown that his philosophical thoughts were of a purely rationalistic character, and, relying not only on the achievements of the individual sciences, but most importantly – on the history of logic and scientific analysis and thinking , because only reason for productive work and need a good man's free will .